Fractional order β-Laplace integral transform. (December 2020) - Gaur, Amit; Agarwal, Garima
Abstract: We introduce a (new) generalized form of β -Laplace integral transform, fractional β -Laplace integral transform, or β -Laplace integral transform of fractional order. The β -Laplace integral transform of fractional order can be applied to functions which are fractional differentiable but are not differentiable. After review some literature on fractional analysis based on the modified Riemann-Liouville derivative, we define the fractional order β -Laplace integral transform, obtain some main properties, convolution property and formula for the inverse of fractional order β -Laplace integral transform.